Fast approximate Bayesian inference of HIV indicators using PCA adaptive Gauss-Hermite quadrature - Adam Howes; Alex Stringer; Seth R. Flaxman; Jeffrey W. Imai–Eaton (Journal of Theoretical Biology, 2026)

Bourbon Barrels and Bottlenecks: a Nuanced Look at Thirty Years of White Oak Population Dynamics - Lance A. Vickers; Benjamin O. Knapp; Thomas Goff; Thomas J. Brandeis; John M. Lhotka; Randall S. Morin; Kenton L. Sena; Jeffrey W. Stringer (Journal of Forestry, 2025)

Sustainability of White Oak ( Quercus alba ) Timber Supply in Kentucky - Gaurav Dhungel; Thomas O Ochuodho; John M Lhotka; Jeffrey W Stringer; Kamana Poudel (Journal of Forestry, 2024)
White oak is a major commercial tree species and an important timber resource in Kentucky. However, current forest inventory trends from the Central Hardwood Forest Region (CHFR) reveal a sustainability threat from declining white oak regeneration and recruitment leading to a disproportionate inventory structure. Using Forest Inventory and Analysis (FIA) data together with the Forest Vegetation Simulator (FVS), we performed a base run analysis of projected inventory levels of white oak sawlogs to better understand whether the inventory level is sustainable to support the current harvest level of white oak in the future. The projections were further examined by tree grades to provide a general outlook on the quality of white oak timber growing in Kentucky’s forests in posterity. By doing so, we generated results that indicate that projected inventory levels of white oak sawlogs cannot be considered sustainable to support current harvest levels from 2058 onwards. In addition, the long-term trends in inventory levels of high-quality white oak sawlogs would be continuously declining whereas that of low-quality sawlogs would be steadily increasing. On the brink of these significant inventory shifts, our study calls for proactive forest management approaches to stabilize the white oak timber resource supply in Kentucky and beyond.

Long-Term Effects of Crop Tree Release on Growth and Quality in White-Oak ( Quercus alba L.)-Dominated Stands - Philip J Vogel; John M Lhotka; Jeffrey W Stringer (Forest Science, 2022)
Crop tree release (CTR) can be an effective intermediate silvicultural treatment for culturing high-value stems in mixed hardwood stands. The lengthy rotation of hardwoods requires long-term evaluations if silvicultural treatment effectiveness is to be fully evaluated. Our study provides a 35-year evaluation of individual-tree and stand response to CTR imposed in small sawtimber-sized white-oak (Quercus alba L.)-dominated stands. The focus on white oak is justified based on the significant biologic and economic values of the species, and this study furthers our ability to optimize use of CTR as management tool for sustaining our oak resources. The replicated experiment included three treatment levels: 20 crop trees ac−1, 34 crop trees ac−1, and a control. Using a repeated-measures framework, we analyzed (1) how CTR affects growth and stem quality of white oak crop trees and (2) stand-level effects of CTR on basal area, stocking, and ingrowth. CTR increased crop tree diameter growth and proportion of crop trees reaching their maximum potential grade. However, crop tree diameter growth and proportion achieving maximum potential grade did not differ between the 20 and 34 crop trees ac−1 treatments. Finally, CTR stimulated stand-wide growth without altering the patterns of ingrowth density or species distributions.

Midstory Removal Facilitates Growth but Reduces Competitiveness of Oak Reproduction Prior to and after Shelterwood Establishment Cutting - Zachary J Hackworth; John M Lhotka; Jeffrey W Stringer (Forest Science, 2020)
This study examined the influence of midstory removal applied 9 years prior to a shelterwood establishment cut on survival, growth, and competitive status of black oak (Quercus velutina Lam.), white oak (Quercus alba L.), and an oak competitor, red maple (Acer rubrum L.), immediately before and at 6 years following shelterwood cutting on intermediate productivity sites in the Central Hardwood Forest Region. We also examined height and density distributions of the regenerating cohort to quantify seedling establishment and to elucidate relative oak competitiveness at each time period. Although oak seedlings were taller 9 years after midstory removal than in undisturbed controls, the midstory removal treatment reduced the frequency of free-to-grow oaks (relative to understory competitors) and increased the size of red maple and relative density of large competitors. Height growth of all three species following establishment cutting was increased by prior midstory removal and dependent on seedling competitive position immediately before shelterwood establishment. Additionally, we observed increased seedling densities 6 years following shelterwood establishment cutting and greater white oak seedling establishment when midstory removal preceded the shelterwood treatment.